2023
DOI: 10.3390/biomedicines11030662
|View full text |Cite
|
Sign up to set email alerts
|

Emerging Therapy for Diabetic Cardiomyopathy: From Molecular Mechanism to Clinical Practice

Abstract: Diabetic cardiomyopathy is characterized by abnormal myocardial structure or performance in the absence of coronary artery disease or significant valvular heart disease in patients with diabetes mellitus. The spectrum of diabetic cardiomyopathy ranges from subtle myocardial changes to myocardial fibrosis and diastolic function and finally to symptomatic heart failure. Except for sodium–glucose transport protein 2 inhibitors and possibly bariatric and metabolic surgery, there is currently no specific treatment … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 348 publications
(366 reference statements)
0
3
0
Order By: Relevance
“…Therefore, further research into the pathogenesis of DCM is essential. Recently, more and more studies have pointed out the crucial importance of autophagy in the pathogenesis of DCM 21 , 22 and suggested that promoting cardiomyocyte autophagy resonance alleviates DCM. 23 , 24 (Figure 2 ).…”
Section: From Dm To Dcmmentioning
confidence: 99%
“…Therefore, further research into the pathogenesis of DCM is essential. Recently, more and more studies have pointed out the crucial importance of autophagy in the pathogenesis of DCM 21 , 22 and suggested that promoting cardiomyocyte autophagy resonance alleviates DCM. 23 , 24 (Figure 2 ).…”
Section: From Dm To Dcmmentioning
confidence: 99%
“…Hyperglycaemia may impair the protein degradation process, collagen included, which leads to increased fibrosis and myocardial stiffness [101]. AGEs bind to the AGE receptors (RAGEs), whose expression increases in diabetic hearts due to oxidative stress [102]. AGEs also release key prosclerotic and proinflammatory cytokines and increase vascular stiffness.…”
Section: Agesmentioning
confidence: 99%
“…AGEs also release key prosclerotic and proinflammatory cytokines and increase vascular stiffness. All these phenomena can be used to partly explain the atherosclerosis and diastolic dysfunction noted in diabetic patients [101,102].…”
Section: Agesmentioning
confidence: 99%